Collaborative governance in strengthening the competitiveness of the Indonesia fisheries industry in preparation for the IEU-CEPA - Ferdian Ahya Al Putra; Ahadina Hanifati Amimah; Nona Berlin Neffertiti Meylim (Masyarakat, Kebudayaan dan Politik, 2026)
This study examines efforts to enhance the competitiveness of Indonesia’s fisheries industry as a preparatory step for implementing the Indonesia-European Union Comprehensive Economic Partnership Agreement. This research is a qualitative study presented descriptively through a literature review, drawing on Collaborative Governance theory and the endowment factor concept in the Heckscher-Ohlin model to analyze stakeholder collaboration in maximizing fisheries products as a leading export commodity to the European Union. The findings indicate that fishery products have not yet contributed optimally to Indonesia’s GDP. Marine capture fisheries and their derivative products account for approximately 7.9% of the GDP. Meanwhile, Indonesia and the European Union have agreed on the IEU-CEPA framework, which opens up significant opportunities for expanding fisheries exports. To take advantage of this opportunity, the Indonesian government needs to strengthen collaboration with multiple stakeholders, particularly in improving the competitiveness of fisheries products. However, several challenges persist, including weak fisheries governance, security concerns, ecosystem degradation, limited access to capital and technology, and difficulties in aligning stakeholder interests. This study recommends a holistic and collaborative approach involving the government as a regulator and facilitator, academia as innovators, the private sector as investors, communities as key implementers, and the media as information disseminators.